2013
DOI: 10.1007/s13191-013-0334-y
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Effect of Three Types of Denture Adhesives on the Retention of Maxillary Denture Bases: An In Vivo Study

Abstract: There are many factors involved in the success of a good quality complete dentures, one of them is retention. There are some forcing situations where providing optimal retention may be a problem, in which use of denture adhesives is recommended. In the present study, primary and secondary impressions were made on 20 completely edentulous patients, master cast was fabricated. Master cast was duplicated; heat-cured denture base was fabricated. The retention test for control group, powder group, wafer group, past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The intergroup analysis showed that there was no statistically significant difference in retentive ability of all denture adhesives at all time intervals (p > 0.05). This is in accordance with Salman and Ibrahim, 12 but the results were contrary to other studies done by Pachore et al, 22 Kumar and Thombare, 15 Chowdhry et al, 14 and Berg et al 30 where paste form of denture adhesives performed better compared with the powder form as the powder form dissolves in saliva and loses its effectiveness with time while paste form has an oily medium, which does not dissolve easily in saliva.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The intergroup analysis showed that there was no statistically significant difference in retentive ability of all denture adhesives at all time intervals (p > 0.05). This is in accordance with Salman and Ibrahim, 12 but the results were contrary to other studies done by Pachore et al, 22 Kumar and Thombare, 15 Chowdhry et al, 14 and Berg et al 30 where paste form of denture adhesives performed better compared with the powder form as the powder form dissolves in saliva and loses its effectiveness with time while paste form has an oily medium, which does not dissolve easily in saliva.…”
Section: Discussionsupporting
confidence: 85%
“…Kapur 27 and Salman and Ibrahim 12 also shared the similar opinion for use of well-fitting denture for the testing of retention. Kumar and Thombare 15 and Pachore et al 22 used only the denture bases for evaluation of retentive ability of the denture adhesives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous clinical studies have shown that the retention of complete maxillary dentures or base plates was measured with specially designed devices that were complex to set up and required space for equipment. [ 1 2 3 4 5 6 7 ] van Kampen et al and Geckili et al used instruments similar to universal testing machines in clinical studies. [ 4 8 ] In addition, portable and small devices have been used in other clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, denture adhesives improve retention and stability for ideal as well as for compromised ridges. [ 6 7 ] However, these adhesives showed carcinogenic changes in the underlying tissues. [ 8 ] This in vivo study was performed to determine the effect of conventional, anchorized, and injection molding processing techniques on the retention of maxillary denture base.…”
Section: Introductionmentioning
confidence: 99%